Potential hypocholesterolemic and health benefitsof Baccaurea angulata fruit in hypercholesterolemic rabbits - Ahmed, Idris Adewale; Mikail, Maryam Abimbola; Ibrahim, Muhammad; Hazali, Norazlanshah; Abdull Rasad, Mohammad Syaiful Bahari; Abdul Ghani, Radiah; Hashim, Ridzwan; Abdul Wahab, Ridhwan; Arief Ichwan, Solachuddin Jauhari; Md Isa, Muhammad Lokman; Draman, Samsul; Ishola, Afeez Adekunle (2014)
INTRODUCTION: The build-up of cholesterol within the lining of the vascular wall alters vascular structure and function thus interfering with endothelial function and leading to plaques, lesions, occlusion, and embolism. Thus, a considerable effort has been made towards evaluating the impact and mechanisms of cholesterol-lowering therapies and interventions for cardiovascular outcomes. Therefore, this work was aimed at evaluating the potential health benefit of Baccaurea angulata (BA) fruit in reducing total cholesterol (TC) in serum, aorta and liver of hypercholesterolemic rabbits. MATERIALS AND METHODS: Different doses of BA (0, 0.5, 1.0, and 1.5 mL juice/kg rabbits/day) representing negative control (NgC), low, medium and high doses were given to rabbits fed high-cholesterol diet for 90 days. The result was compared with normal control (NC) group fed commercial pellet only. The serum was obtained from the blood taken at the beginning and end of the experimental period. Rabbits’ liver and thoracic aortas were also homogenized and analysed. RESULTS AND DISCUSSION: The administration of low, medium and high doses of BA fruit juice to high-cholesterol fed rabbits resulted in 21.37, 35.54 and 30.21% reduction in serum TC respectively relative to the negative control. The atherogenic rabbits receiving 1.0 and 1.5 mL/kg/day also had a significant dose-dependent reduction (p<0.05) in their aortic and hepatic TC levels. The aortic TC of the medium and high doses groups were 1.17±0.38 and 1.07±0.32 mmol/L respectively, compared to the NgC and 0.5 mL/kg/day groups with 2.37±0.06 and 1.87±0.55 mmol/L aortic TC respectively. CONCLUSION: Though, the mechanism involved in the reduction of TC in the rabbit serum, liver and aorta by the diet supplementation with BA is yet to be clearly understood, the protective and hypocholesterolemic capacity of BA may be attributed to its antioxidant action thereby attenuating the consequent damage to the heart tissue. Therefore, BA fruit possesses hypocholesterolemic and antioxidant properties.